Parental paternalism and patience - Lukas Kiessling; Shyamal K. Chowdhury; Hannah Schildberg-Hörisch; Matthias Sutter (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2021)
We study whether and how parents interfere paternalistically in their children's intertemporal decision-making. Based on experiments with over 2,000 members of 610 families, we find that parents anticipate their children's present bias and aim to mitigate it. Using a novel method to measure parental interference, we show that more than half of all parents are willing to pay money to override their children's choices. Parental interference predicts more intensive parenting styles and a lower intergenerational transmission of patience. The latter is driven by interfering parents not transmitting their own present bias, but molding their children's preferences towards more time-consistent choices.
Keywords: C90; D1; D91; D64; J13; J24; O12; 330; Parental paternalism; Time preferences; Convex time budgets; Present bias; Intergenerational transmission; Parenting styles; Experiment